2019
DOI: 10.5296/ijhrs.v9i3.14973
|View full text |Cite
|
Sign up to set email alerts
|

A Welfare Model of Street Vendors: Cases from Denpasar, Bali, Indonesia

Abstract: This study determines the socio-economic characteristics of street vendors in Denpasar, Bali, Indonesia and proposes a welfare model to examine their well-being. The results showed that street vendors in Denpasar are mostly male, married, with an average age of 39. Most are recent migrants who rent their housing. The majority sell food and beverages from carts and work almost 8 hours per day. Most are self-employed and may be assisted by family labor. Most do not do bookkeeping for their business activities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These programs are essential to ensuring that the food sold by street vendors is safe to eat and that hygiene regulations are followed (Monney et al, 2013). Furthermore, research highlights the need of augmenting the abilities and proficiencies of street food sellers via instruction, dissemination of knowledge, and infrastructural assistance in order to enhance their output and competitiveness (Nilakusmawati et al, 2019). Such initiatives to empower street vendors and increase their economic options might be implemented with assistance from NGOs.…”
Section: Ngo In Street Food Developmentmentioning
confidence: 99%
“…These programs are essential to ensuring that the food sold by street vendors is safe to eat and that hygiene regulations are followed (Monney et al, 2013). Furthermore, research highlights the need of augmenting the abilities and proficiencies of street food sellers via instruction, dissemination of knowledge, and infrastructural assistance in order to enhance their output and competitiveness (Nilakusmawati et al, 2019). Such initiatives to empower street vendors and increase their economic options might be implemented with assistance from NGOs.…”
Section: Ngo In Street Food Developmentmentioning
confidence: 99%
“…The role of PKL as the informal economy which can absorb excess labor from a rural area on the urbanization process is explained by BPN (2020), Rini (2013), Nilakusmawati, Susilawati, andWall (2019), andHariyatno et al (2020). PKL is needed by people (Widjajanti 2015) even for the government (Tahir and Riskasari 2015) and they can pay the rent cost to the survival of their business (Benítez et al n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…The recommendation put forward is that there is a need for better handling of women who work in the informal sector, so that it will create a high economic potential for family welfare, and it is necessary to handle it with sustainable policies and provide greater access to formal capital sources. Furthermore, Nilakusmawati, Susilawati, & Wall [19] modeled the income of street vendors using socio-economic characteristics. It was found that the variables that influenced street vendors' income were marital status, age, employment status, physical facilities, and the presence/absence of bookkeeping of business activities.…”
mentioning
confidence: 99%